Effect of ventricular tonicity upon cerebrospinal fluid production in rabbits. - Pullen, R G (1985)
Ventriculo-cisternal perfusion in rabbits has been employed to examine steady-state relations between ventricular sodium and water fluxes and ventricular osmolality. These fluxes have been determined in individual rabbits when the ventricular fluid was either similar to normal cerebrospinal fluid (c.s.f.) or when its osmolality was changed to one value within the range of about 150-300 mosmol/l. The ventricular osmolality was changed by perfusing the ventricles with sucrose solutions of different concentrations that were either ion free, contained a low concentration of sodium, or contained both sodium and furosemide to inhibit the active production of c.s.f. Results suggest that this experimental range of ventricular osmolality is without significant effect upon a constant active sodium-coupled water movement into the ventricles, whereas a passive osmotic water flux into the ventricles increases with ventricular osmolality.